The Improving Elementary School Teachers’ Skills in Scientific Publication Writing through Coaching Clinics - Afrilianti, Alviani; Sianturi, Risbon; Kadarsah, Deni (International Conference on Elementary Education, 2024)
The ability to write scientific publications among elementary school teachers is still relatively low as a result of the lack of basic skills and self-confidence of teachers in writing as well as the lack of facilities and media for scientific publications in the school, necessitating the need for coaching that one of which can be done through a coaching clinic program. To understand and analyze the role and implementation of coaching clinics in writing of scientific publications, this research was conducted by applying action research methods to elementary school teachers which included two research cycles. The results found that implementing a coaching clinic for writing scientific publications can be carried out as long as the Principal has the commitment and ability to carry it out. Apart from that, the Principal must also ensure that his actions can bring about the desired changes, especially to quickly improve teacherâ€™s competence and performance. The application of this coaching method can improve teachers’ skills in writing scientific papers, compiling ideas and developing better linguistic structures in writing. Thus, it can be concluded that the implementation of a coaching clinic for writing scientific publications can play a positive role in improving the writing skills of elementary school teachers.